2021
DOI: 10.1002/iid3.570
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of fecal microbial transplantation treatment in adults with moderate‐to‐severe atopic dermatitis

Abstract: Background: Atopic dermatitis (AD) is a remitting relapsing chronic eczematous pruritic disease. Several studies suggest that gut microbiota may influence AD by immune system regulation. Methods: We performed the first in-human efficacy and safety assessment of fecal microbiota transplantation (FMT) for AD adult patients. All patients received 2 placebo transplantations followed by 4 FMTs each 2 weeks apart.AD severity and fecal microbiome profile were evaluated by the Scoring Atopic Dermatitis Score (SCORAD),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 41 publications
(40 reference statements)
0
45
0
Order By: Relevance
“…That the gut microbiota is an important player in the disease pathogenesis was recently shown by interventional studies using fecal microbial transplantation (FMT) in patients with AD. These studies showed that FMT is safe and efficacious in controlling clinical signs of AD in dogs and humans [ 32 , 33 ]. Therefore, there is a high need for future studies in this field.…”
Section: Discussionmentioning
confidence: 99%
“…That the gut microbiota is an important player in the disease pathogenesis was recently shown by interventional studies using fecal microbial transplantation (FMT) in patients with AD. These studies showed that FMT is safe and efficacious in controlling clinical signs of AD in dogs and humans [ 32 , 33 ]. Therefore, there is a high need for future studies in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to baseline pre-FMT, the authors reported a decrease in corticosteroid usage, a decrease in disease severity, and the patient’s gut microbiota profile becoming similar to the donor’s. Interestingly, the level of similarity correlated with the decreases in disease severity, namely, the more the profile was similar to the donor and the more the severity decreased [ 206 ]. Despite the variability of the results obtained in a small cohort of patients, this is the first clinical evidence demonstrating promising FMT-based therapy perspectives for the treatment of atopic dermatitis.…”
Section: Fecal Microbiota Transplantation In Human Diseasesmentioning
confidence: 99%
“…Indeed, evidence has suggested that oral supplementation of Lactobacillus and Bifidobacterium strains could reduce the risk of AD in infants by regulating T cell-mediated responses [157]. FMT, as the most direct approach of modulating gut microbiota, is reported to be associated with suppression of AD-induced allergic responses by restoration of gut microbiota and immunological balance both in human and animal studies [158,159].…”
Section: The Role Of Skin and Gut Microbiota In Atopic Dermatitismentioning
confidence: 99%